The The Doctrine of The Trinity And Its Implications for Everyday Worship - Galvin Hermawan (JOURNAL of THEOLOGICAL STUDENTS, 2026)
The primary purpose of this study is to explain and reflect the doctrine of the Trinity in the daily worship of believers. As divinely revealed in Scripture and understood in historical Orthodox Christianity, the doctrine of the Trinity should influence and shape the daily worship of believers to God. The implications of this doctrine for daily worship can be seen in at least three main areas. First, the object of our worship is the Triune God Himself, or God understood as three persons rather than just one. Second, when believers give thanks to God, they need to show affection for each person of the Trinity. Third, this doctrine evokes awe and humility in the hearts of believers as they reflect on it in worship.